2014
DOI: 10.1055/s-0033-1341018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Organic Substrates with RuIV=O Complexes Formed by Proton-Coupled Electron Transfer

Abstract: We describe our recent progress in mechanistic investigations on substrate oxidation reactions with Ru IV =O complexes having pyridylamine ligands. The Ru IV =O complexes are synthesized from the corresponding Ru II -OH 2 complexes either through a proton-coupled electron-transfer procedure using a cerium(IV) complex as an oxidant or by bulk electrolysis. We have verified the presence of an adduct-formation equilibrium between the Ru IV =O complex and a substrate in water, which strongly affects the reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As an electron donor, a Ru II –polypyridyl complex bearing a carboxyl group at the periphery ( Ru II COOH ) has been selected to form a hydrogen-bonded supramolecular assembly with H 4 DPP 2+ . In addition to the electron-donating ability of Ru II COOH , the complex would also be the precursor of an oxidation catalyst in supramolecular hetero-triads enabling photocatalytic oxidation reactions. , On the other hand, benzyl viologen ( BV 2+ ) derivatives have been employed as an electron acceptor because of the high reduction potentials . Note that the one-electron-reduced species ( BV •+ ) is relatively stable, enabling to form a long-lived ET state in supramolecules.…”
Section: Introductionmentioning
confidence: 99%
“…As an electron donor, a Ru II –polypyridyl complex bearing a carboxyl group at the periphery ( Ru II COOH ) has been selected to form a hydrogen-bonded supramolecular assembly with H 4 DPP 2+ . In addition to the electron-donating ability of Ru II COOH , the complex would also be the precursor of an oxidation catalyst in supramolecular hetero-triads enabling photocatalytic oxidation reactions. , On the other hand, benzyl viologen ( BV 2+ ) derivatives have been employed as an electron acceptor because of the high reduction potentials . Note that the one-electron-reduced species ( BV •+ ) is relatively stable, enabling to form a long-lived ET state in supramolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although the inherent paramagnetism of the hexacoordinated Ru IV ]O species (S = 1), X-band EPR of Ru IV ]O generally exhibit no EPR signal because of a large spin coupling exhibited in a zero magnetic eld. [65][66][67][68][69][70][71][72][73][74][75][76] Mukai reported that a powder sample of 2,6di-tert-butyl-4-phenyl phenoxyl radical displayed a sharp EPR signal at g = 2.0047. 77 In solution, both the 2,6-di-tert-butyl-4phenyl phenoxyl radical and the 2,4,6-di-tert-butyl phenoxyl radical demonstrated EPR signals at g = 2.0044 and 2.0046, Scheme 1 Redox behavior of [1] 2+ at pH < 9.8 (upper) and pH > 9.8 (lower).…”
Section: Assignment Of the Oxidized Form Of [1] 2+mentioning
confidence: 99%
“…A number of studies on the electronic structures, catalytic oxidation reactions and model reactions with sMMO analogues with diiron centers, 2 or some with dinickel centers 3 have been reported in homogeneous systems, which are not limited to the rich chemistry of mononuclear metal–oxido species by, e.g. the 8 th group iron, 4 ruthenium, 5 and osmium 6 centers. However, reports on those with diruthenium centers are limited although, only recently, a light-driven methane monooxygenation with the dinuclear Ru( iv )–Ru( iv ) complex was reported.…”
Section: Introductionmentioning
confidence: 99%